Dynamics of religion in Southeast Asia: magic and modernity - Gottowik, Volker (Global Asia, 2014)
Starting from the premise that modernity has cast a spell over people around the world, this collection explores the use of magic and religion as modern tools for connection. The contributors draw on new ethnographic research in Vietnam, Laos, Thailand, and Indonesia to show that residents of these countries no longer see religion and modernity as contradictory. Rather, religious ideas and magic practices help people across the region to meet the challenges of modern life. Revising our understanding of religion in Southeast Asia, this collection sheds new light on the multiple modernities that characterize our globalized world
Includes bibliographical references
Keywords: Southeast Asia -- Religion; Aufsatzsammlung; Religiöses Leben; Religion; Südostasien